INVITRO ANTIBACTERIAL ACTIVITY OF SOME MEDICINAL PLANTS AGAINST PATHOGENS CAUSING URINARY TRACT INFECTION (UTI). - Beenish Ilyas; Faqir Hussain Khan; Aazha Maqbool et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:The present study was done to compare the antibacterial activity of Coriandrumsativum, Trigonella foenum-graecum, Menthapiperitaand Spinaciaoleraceaagainst pathogens (Escherichia coli, Klebsiella, Pseudomonas aurogenosa, Staphylococcus aureus) that causes UTI. Leaves and stems of all the plants were used. The disk diﬀusion method was applied for antibacterial assay. Ciproﬂoxacin was used as a standard. The study revealed that the aqueous extracts of all the plants had higher antibacterial activity against bacterial pathogens as compared to ethanol extracts. Mentha piperita showed higher zone of inhibitions whereas Spinacia oleracea showed lower zone of inhibition values among all the plants against bacterial strains.